The Influence Of Shopee Paylater, Shipping Vouchers And Shopee Application Flash Sales On User Purchasing Decisions In The Manna City Area South Bengkulu District - Sulistia, Zahra; Soleh, Ahmad; Febliansa, M Rahman (Universitas Dehasen Bengkulu, 2025)
Technological innovation in the form of software applications that facilitate shopping activities has been created, one of which is the Shopee application. In the Shopee application there are various offer features that function to attract customers and make shopping easier for customers. The various offer features provided and the most prominent from Shopee are. shopee paylater, Shipping Vouchers and Flash Sale. The purpose of this study is the influence of Shopee paylater, Shipping Vouchers and Flash Sale on user purchasing decisions in the Manna City area, South Bengkulu Regency. The research method used is quantitative, the data collection technique in this study is the questionnaire technique, with a research sample of 50 respondents. The results of the study showed that multiple linear regression 8,065 + 0.311 X1 + 0.311 X2 + 0.991 X3 +1,874. Where the coefficient is positive, meaning that there is a positive orunidirectional relationship between the variables Shopee Paylater (X1), Shipping Voucher (X2) Flash Sale (X3), the value is 0 (zero), purchasing decisions (Y) of users in the Manna City area, South Bengkulu Regency. The results of the Shopee Paylater test (XI) show t count 1.718> t table 1.675 and a significance of 0.048<0.05, then the results of the Ha hypothesis are accepted and Ho is rejected, meaning that Shopee Paylater has a positive and significant effect on user purchasing decisions in the Manna City area, South Bengkulu Regency. The results of the Shipping Voucher test (X2) show t count 1.808> t table 1.675 and a significance of 0.047 <0.05, then the results of the Ha hypothesis are accepted and Ho is rejected, meaning that Shipping Voucher has a positive and significant effect on user purchasing decisions in the Manna City area, South Bengkulu Regency. The results of the Flash Sale test (X3) show t count 8.694> t table 1.675 and significance 0.000 <0.05, then the results of the hypothesis Ha are accepted and Ho is rejected, meaning Flash Sale has a positive and significant effect on user purchasing decisions in the Manna City area, South Bengkulu Regency. Based on the comparison of the F count value with the F table, the F count value is greater than the F table value, which is 45.633> 2.79, so it is concluded that the hypothesis is accepted, meaning that there is a simultaneous influence between Shopee Paylater (XI), Shipping Vouchers (X2), Flash Sale (X3) on Purchasing Decisions (Y) of users in the Manna City area, South Bengkulu Regency. This can be seen at a significance level of 0.000 <0.05.